2008
DOI: 10.1017/s1751731108002279
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and milk yield losses associated with lameness in Holstein-Friesian dairy cattle

Abstract: Weekly locomotion scores on a scale of 1 to 5 were used to investigate the relationship between cattle lameness, management systems and the impact of lameness on milk production. The data were 14 026 locomotion scores from 248 Holstein-Friesian cows. Cows were managed in two groups, XE (high-concentrate feed and housed indoors all year) and XM (low-concentrate feed and outdoors in summer). Analysis was performed using residual maximum likelihood. Results indicated that the most significant variables affecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 29 publications
1
34
0
4
Order By: Relevance
“…Using body fat reserves for milk production entails mobilizing fat from many tissues, including the digital cushion [8] . Other studies have also revealed a connection between a lower BCS and lameness [6,10,12,21] , as well as a connection between a higher BCS and a higher LS [22] . In a prospective longitudinal study, Randall et al [23] found that a low BCS predisposes cows to lameness and that maintaining a BCS ≥2.5 is optimal for reducing the risk of a lameness event.…”
Section: Discussionmentioning
confidence: 91%
“…Using body fat reserves for milk production entails mobilizing fat from many tissues, including the digital cushion [8] . Other studies have also revealed a connection between a lower BCS and lameness [6,10,12,21] , as well as a connection between a higher BCS and a higher LS [22] . In a prospective longitudinal study, Randall et al [23] found that a low BCS predisposes cows to lameness and that maintaining a BCS ≥2.5 is optimal for reducing the risk of a lameness event.…”
Section: Discussionmentioning
confidence: 91%
“…Leach et al, 2005). A more gradual step-up in concentrates had a positive effect on IDHE and DD (Somers et al, 2005a and2005b) and a high concentrate diet has been found to have a negative effect on DD (Olmos et al, 2009) and locomotion score (Onyiro et al, 2008). Sufficient levels of minerals in the feed are known to be essential in improving hoof quality.…”
Section: Estimating Effects Of Intervention Measuresmentioning
confidence: 99%
“…Herds with earlier age at first calving had more lameness ). There are more lame cows in intensively managed groups (Onyiro et al, 2008) …”
Section: Multifactorial: Degree Of Intensificationmentioning
confidence: 99%
“…Many studies have found a correlation between hoof lesions (sole ulcers and white line disease) or diseases (interdigital necrobacillosis) and high average milk production (Alban et al, , 1996Bergsten, 2003;Mulligan et al, 2006;Amory et al, 2008;Onyiro et al, 2008;Rutherford et al, 2009;Brenninkmeyer et al, 2013;Richert et al, 2013b). Mineral deficiencies and negative energy balance that may lead to a thinner digital cushion occur frequently, predisposing cows with high production to foot lesions (Collard et al, 2000;Bicalho et al, 2009;Trevisi et al, 2012;Nielsen et al, 2013).…”
Section: Output: Milk Yield Per Cowmentioning
confidence: 99%